A Risk-Based Approach to Planning the Elaboration of Pharmacopoeial Monographs - A. V. Yarutkin; V. L. Bagirova (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Scientific relevance. This article describes a risk-based analysis of the need for elaborating pharmacopoeial requirements for 6 therapeutic groups of medicines, including an evaluation of the range and number of batches of these medicines put into the stream of commerce in the Russian Federation and a comparison of the corresponding product specification files and quality standards. The  article presents a  set of criteria for planning the elaboration of monographs for the State Pharmacopoeia of the Russian Federation according to a risk-based approach, which is used in a variety of other fields.Aim. The study aimed to develop a comprehensive multivariate risk-based system providing criteria for planning the  elaboration of monographs for the  State Pharmacopoeia of the Russian Federation.Materials and methods. This study focused on medicines for human use under a  range of international non-proprietary names. The  authors analysed entries in the Russian State Register of Medicines, data on the number of batches released to the pharmaceutical market, and product specification files and quality standards. The study was conducted using literature search, data analysis, and system-oriented methods.Results. According to the results, a multivariate risk-based analysis is needed for planning the elaboration of monographs for the State Pharmacopoeia of the Russian Federation and the subsequent prioritisation of therapeutic groups or individual medicines for their standardisation.Conclusions. The  suggested risk-based system for planning the  elaboration of monographs for the  State Pharmacopoeia of the  Russian Federation includes the following criteria: the social significance of a medicinal product and its value for the  health care system; the  percentage of medicinal products not tested by the national regulatory authority at the level of active pharmaceutical ingredients; the substantial number of batches and the significant range of medicinal products and the  respective active pharmaceutical ingredients by different manufacturers present in the pharmaceutical market; and the analytical procedures and requirements established in product specification files and quality standards.